P130 Assessing the roles of inferior parietal lobule and ventral premotor cortex in emotion body processing: a combined cTBS-fMRI study. Issue 3 (March 2017) - Engelen, T.; Zhan, M.; Sack, A.; de Gelder, B.
Abstract : Introduction: The perception of emotion stimuli in the environment prepares our bodies for action, and especially when confronted with whole body expressions of an emotion like anger, action-related areas in the brain are triggered. Previously, parietal dorsal stream and premotor areas have been linked as crucial areas for processing of such stimuli, but questions about their contributions and specificity within the body processing network remain. Objectives: We set out to disentangle the respective roles of dorsal stream areas crucial for action observation (inferior parietal lobule (IPL)) and premotor areas involved in action preparation (ventral premotor cortex (PMv)) in the processing of emotional bodies by assessing local as well as remote effects of cTBS stimulation within the body processing network. Methods: Seventeen participants completed the experiment, which consisted of three fMRI sessions. Functional images were acquired using a 3T scanner with a 64-channel head-neck coil. During each session a passive viewing task was performed in which blocks of short videoclips of actors performing a neutral or angry action were presented. Two of the sessions were preceded by neuronavigated cTBS stimulation over either rIPL or rPMv based on individual anatomy. One session was used to assess baseline activity. During the baseline session two functional localizers were acquired to determine regions of interest (ROI). Functional ROIs include bilateral extrastriate body area (EBA), right temporoparietal junction (rTPJ), and right posterior superior temporal sulcus (rpSTS). Results: Preliminary results of five participants hint at a general decreased response to both angry and neutral bodies in three of the functionally defined regions of interest (lEBA, rTPJ and rpSTS). Further analysis will focus on anatomically defined ROIs representing the areas stimulated (rIPL and rPMv), as well as whole brain group analysis comparing the three sessions. Conclusions: Initial results confirm the involvement of rIPL and rPMv in the processing of dynamic body stimuli. Stimulation of these areas has previously shown effects on the behavioural level, the results of the current experiment will extend these results by showing how also remote areas involved in body processing are affected by stimulation.